Effect of Margin Designs on the Marginal Adaptation of Zirconia Copings - Syed Rashid Habib; Mohammed Ginan Al Ajmi; Mohammed Al Dhafyan; Abdulrehman Jomah; Haytham Abualsaud; Mazen Almashali (University of Zagreb. School of Dental Medicine, 2017)
Objective: The aim of this in vitro study was to investigate the effect of Shoulder versus Chamfer margin design on the marginal adaptation of zirconia (Zr) copings. Materials and Methods: 40 extracted molar teeth were mounted in resin and prepared for zirconia crowns with two margin preparation designs (20=Shoulder and 20=Chamfer). The copings were manufactured by Cercon® (DeguDent GmbH, Germany) using the CAD/CAM system for each tooth. They were tried on each tooth, cemented, thermocycled, re-embedded in resin and were subsequently cross sectioned centrally into two equal mesial and distal halves. They were examined under electron microscope at 200 X magnification and the measurements were recorded at 5 predetermined points in micrometers (µm). Results: The overall mean marginal gap for the two groups was found to be 206.98+42.78µm with Shoulder margin design (Marginal Gap=199.50+40.72µm) having better adaptation compared to Chamfer (Marginal Gap=214.46+44.85µm). The independent-samples t-test showed a statistically non-significant difference (p=.113) between the means of marginal gap for Shoulder and Chamfer margin designs and the measurements were recorded at 5 predetermined points for the two groups. Conclusions: The Chamfer margin design appeared to offer the same adaptation results as the Shoulder margin design.